A NEW DESIGN of SIX- PHASE ROTARY CONVERTER ELECTRIC MACHINE - Mohammed, K. G.; Ramli, A. Q.; Ungku Amirulddin, U. A. (International Journal of Integrated Engineering, 2012)
The aim of this research is to design a new ac rotary converter machine to convert the ac single phase voltage to six-phase voltages by using multi stages energy conversion machine. The rotary converter is composed from two main stages and is combined into one frame. These two stages are formed from three main electromagnetic components. The first component represents the input stage that enables the energy from single phase to enter and transformed by the second and third components electro-magnetically to produce six-phase voltages which at the output stage. The programs are created using MATLAB in order to calculate the required dimensions of the converter machine and its parameters for magnetic and electrical circuits.